PENGARUH GAYA HIDUP SEHAT UNTUK MENGATASI TURNOVER INTENTIONS YANG TERJADI DI AKUNTAN PUBLIK - Paramitha, Novena Mayayu (Jurnal Akuntansi Bisnis, 2014)
The aim of this research is to test the effect of job stress as a mediating influence between healthy lifestyle and turnover intentions of auditors in public accounting. Public Accounting Firm (KAP) as a professional company is required to have a competitive advantage to survive and win the competition. The main resource in the KAP is the auditor. One of the serious problems in the KAP is the high wants the auditor to change jobs due to the high work stress which causes the Firm must pay due to the high cost of training for new auditors and that problem need to find a solution immediately. According to Robbins (2002), the most ideal approach is with individual approach which is healthy lifestyle were selected to help reduce the stress experienced by the work that can also influence to suppress turnover intentions. The respondents on this research are drawn from all auditors in public accountant in Semarang. The results show job sress can be a mediating for influence between healthy lifestyle and turnover intentions which means when the auditors applied a great healthy lifestyle, job stress can be reduced so that the auditorâs turnover intentions.